Reduced cortical plasticity and GABAergic modulation in essential tremor. Issue 4 (21st January 2014) - Chuang, Wen‐Li; Huang, Ying‐Zu; Lu, Chin‐Song; Chen, Rou‐Shayn
ABSTRACT Essential tremor (ET) is the most common movement disorder among adults. Cerebellar dysfunction is thought to be involved in the pathogenesis of ET; however, imaging, electrophysiological studies, and clinical observations have suggested that the cerebral cortex also may participate. We sought to investigate the possible motor cortical contribution to ET by assessing response to continuous theta‐burst stimulation (cTBS), a recognized tool that can produce transient plastic changes, in the primary motor and premotor cortex of patients with ET. We compared parameters, including motor‐evoked potential amplitude, cortical silent period, and short‐interval intracortical inhibition, before and after applying cTBS in healthy controls and patients with ET. We found that, although cTBS applied to either the motor or premotor cortex was capable of producing a suppressive effect on motor cortical excitability in ET patients, the effects lasted for a significantly shorter time compared with the effect produced in healthy individuals. The change seen in measures of intracortical inhibition after motor cortical or premotor cTBS in healthy controls was reduced or absent in the ET patients. Tremor amplitude was decreased significantly after applying cTBS over either the motor or premotor cortex, but the tremor frequency remained unchanged. These findings suggest that inhibitory circuits within the motor cortex are aberrant and less modifiable in ET patients. The reduced plasticity in response to motor and premotor TBS supports the theory of abnormal gamma‐aminobutyric acid (GABA) modulation in ET. © 2014 International Parkinson and Movement Disorder Society